REGIONAL SPENDING EFFECTIVENESS AND FISCAL INDEPENDENCE: A STUDY OF EAST JAVA PROVINCE - Putranda Zahid Fajduani; Mazro’atus Sa’adah (International Journal of Social Science, Educational, Economics, Agriculture Research and Technology (IJSET), 2025)
This study aims to evaluate the effectiveness of regional budget (APBD) expenditure in East Java Province and to analyze its fiscal independence. Data were obtained from the Budget Realization Report (LRA), the Central Bureau of Statistics (BPS), and the Directorate General of Fiscal Balance (DJPK). The study employs a descriptive quantitative method using the effectiveness ratio as the main analytical tool. The findings indicate that East Java's budget expenditure in 2022–2023 was categorized as very effective, with realization levels consistently above 93%. However, fiscal independence remains weak as local revenue (PAD) contributes only about 6–7%, while dependency on central government transfers reaches approximately 64%. This reveals that high expenditure effectiveness does not automatically imply strong fiscal autonomy. A comparison with Central Java and Bali shows similar patterns: high expenditure effectiveness accompanied by limited fiscal independence. These findings highlight that the main challenge of fiscal decentralization in Indonesia lies not in spending absorption but in strengthening local revenue capacity and improving the quality of expenditure, particularly in capital spending.